Korelasi Klasifikasi Penutup Lahan dengan Debit Puncak di Daerah Aliran Sungai - Sachro, Sri Sangkawati; Edhisono, Sutarto; Atmodjo, Pranoto Samto; Prasetyo, Wahyu (MEDIA KOMUNIKASI TEKNIK SIPIL, 2017)
Many studies have shown that land use changes in watersheds such as forests that convert to settlements, industrial and estates, have an impact on flooding. So it is important to know the correlation between the various land use changes to the discharge within a watershed. This study is a preliminary study in an attempt to assess the correlation between land cover index and peak discharge, with case studies in the Beringin River Basin.The peak discharge with the return period of 2, 5, 10, 20, 50 and 100 years are computed with HEC-HMS software, developed by Hydrologic Engineering Centre (HEC) and US Army Corps of Engineers which computes the runoff discharge from the precipitation. As for land covered index (LCI), it is defined as the sum of the land-use index (LUI). The result of the case study shows the strong correlation between the land covered index with the the runoff discharge with such relation : Q100 = -22.42LCI2 + 214.30LCI - 10.62, Q50 = -18.33LCI2 + 181.87LCI - 20.19, Q20 = -14.30LCI2 + 145.27LCI - 15.61, Q10 = -11.36LCI2 + 118.41LCI - 12.29, Q5 = -8.42LCI2 + 91.27LCI - 8.9 and Q2 = -4.44LCI2 + 53.54LCI - 4.5.